Порівняння методів оцінювання складних систем - Поліщук, Д.O.; Поліщук, О.Д.; Яджак, М.С. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Methods to evaluation of complex objects and processes and main areas of its application are considered. Necessity is substantiated and method of the search of unsatisfactorily function elements of complex systems on the base of multi parameters and multi criterion analysis of its behavior is proposed.